2020
DOI: 10.1111/ijfs.14722
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the phase inversion of a turmeric oil nanoemulsion in antifungal process

Abstract: A phase inversion of essential oil nanoemulsion droplets from oil‐in‐water to water‐in‐oil types during moisture evaporation after spraying onto plant leaves is one of the primary mechanisms to expose the essential oil in ambient environment and to play its antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…While this method is not yet widely used in ophthalmic nanoemulsion characterization, it will definitely be adopted in the near future, providing novel insight into structure of colloidal nanosize drug delivery systems. 88 90 …”
Section: Ocular Nanoemulsions Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this method is not yet widely used in ophthalmic nanoemulsion characterization, it will definitely be adopted in the near future, providing novel insight into structure of colloidal nanosize drug delivery systems. 88 90 …”
Section: Ocular Nanoemulsions Research Methodsmentioning
confidence: 99%
“…Although classical electron microscopy techniques (TEM or SEM) require staining and/or drying of nanoemulsions that may affect the size and shape of the nanodroplets, a cryoEM provides the unique oportunity to directly image the obtained colloidal systems without major structural changes. While this method is not yet widely used in ophthalmic nanoemulsion characterization, it will definitely be adopted in the near future, providing novel insight into structure of colloidal nanosize drug delivery systems. …”
Section: Ocular Nanoemulsions Research Methodsmentioning
confidence: 99%
“…Similarly, a turmeric-based oil-in-water nanoemulsion was prepared and applied to determine its antifungal activity against Podosphaera xanthii. The results of the study revealed that the turmeric oil nanoemulsion of turmeric inhibited fungus growth and showed a remarkable antifungal effect [96].…”
Section: Nanoemulsionsmentioning
confidence: 99%